UTILIZING ZISWAF AS AN INSTRUMENT FOR FINANCIAL INCLUSION AND POVERTY REDUCTION EFFORTS - Holle, Mohammad H.; Manilet, Aisa; Nur Asyiah, Binti; Ismail, Syed (Fakultas Ekonomi Dan Bisnis Islam IAIN Metro, 2024)
The government implements various poverty alleviation policies, Ziswaf has not been utilized as an instrument of financial inclusion in poverty alleviation. This study aims to examine and provide solutions to poverty alleviation by making Ziswaf an instrument of financial inclusion. Field research with a qualitative descriptive thinking paradigm makes the Takmir community the subject of the interview and scattered mosques the main object. In addition to the OJK report, Bank Indonesia, Puskas Baznas, and KNEKS are its supporters. The results of the study found that Ziswaf's potential is very large, but the Ziswaf funds distributed have not been able to alleviate poverty. Access and availability of Ziswaf funds are still very scarce and difficult for the community to obtain, the distribution is incidental and consumptive rather than productive. Ziswaf as an instrument of financial inclusion is expected to be managed on target to alleviate poverty.